Self-assembly of caragana-based nanomaterials into multiple heteroatom-doped 3D-interconnected porous carbon for advanced supercapacitors - Zhi-Wen Zhang; Cui-Ying Lu; Guang-Hui Liu; Yuan-Jia Cao; Zhen Wang; Ting-ting Yang; Yu-Hong Kang; Xian-Yong Wei; Hong-Cun Bai (Materials Today Advances, 2023)
This work prepared porous carbon with excellent electrochemical performance using hydrothermal and carbonization methods. Specifically, caragana was used as carbon precursor, hydrazine hydrate as nitrogen source, and nickel acetate as nickel source during this preparation process. The results showed that porous carbon carbonized at 700 °C has excellent surface area (1779 m2 g−1), moderate oxygen content (7.88 at%), and nitrogen content (1.64 at%), which are conducive to improving pseudocapacitance. The N4NiPC180-3 has specific capacitance of 427 F g−1 at 0.5 A g−1, and high capacitance retention of 74.3% even at 20 A g−1. The retention rate after 10,000 cycles is 97.4%, verifying its excellent cycling stability. In addition, the N4NiPC180-3 in the two-electrode system test can achieve an energy density of 35.8 W h kg−1 at a power density of 500.1 W kg−1. This work extends high value-added utilization of biomass derivatives in energy storage applications.